(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2023)
Generally Black Cotton Soil exhibits undesirable engineering properties like shrinkage and swelling properties losses its strength, when come in contact with water. Thereby poor bearing capacity and higher compressibility. Thus the improvement of soil at a site is indispensable. There are many methods and stabilizers to improve the strength of soil like jute, gypsum, fly ash. Rice-husk ash. Cement, lime, used rubber tyres etc. In the present study, we added Waste Foundry Sand and Crushed Waste Glass as stabilizer to improve the properties of Black Cotton soil. Black Cotton Soil used in this project work is carried from Maharashtra. The objective of this study is to improve the strength of the Black Cotton soil by making Soil- Waste Foundry Sand and Soil- Waste Foundry Sand Crushed Glass Powder mixture. Specimens is to be prepared to investigate the properties of soil out of these specimens are prepared by Replacing 2 %, 4%, 6% . Waste Glass Powder with varying percentage Waste Foundry Sand as 10%,20%, 30%.[4] Modified Proctor Test, CBR test and Free Swell Index test is to be conducted to analyze the Optimum Moisture Content (OMC), Maximum Dry Density (MDD) and compressive strength of soil mixture, CBR value and Free Swell Index.